2004
DOI: 10.1080/1470329032000172748
|View full text |Cite
|
Sign up to set email alerts
|

Using e-learning dialogues in higher education

Abstract: Dialogue is arguably one of the most important components of any learning process. However, as student numbers increase and more emphasis is given to electronic delivery of courses, opportunities for effective dialogue may be missed. The technology to support e-learning dialogue is readily available, but design of the dialogue structures and understanding of learners' online communication behaviour requires further research. This paper reports on a study of the use of asynchronous discussion forums to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 10 publications
2
54
0
1
Order By: Relevance
“…Researchers agree that interaction is essential to students' learning experiences and achievement (Laurillard 2000;Garrison and Anderson 2003). Learners learn more effectively if they are actively involved in the process rather than being passive thinkers (Webb et al 2004). Not only did flipped learning in this study allow students to interact with me, the instructor, before, during, and after class, they were also able to interact with the classroom teacher they observed each week and interact with other students from class.…”
Section: Iscussion Benefitsmentioning
confidence: 97%
“…Researchers agree that interaction is essential to students' learning experiences and achievement (Laurillard 2000;Garrison and Anderson 2003). Learners learn more effectively if they are actively involved in the process rather than being passive thinkers (Webb et al 2004). Not only did flipped learning in this study allow students to interact with me, the instructor, before, during, and after class, they were also able to interact with the classroom teacher they observed each week and interact with other students from class.…”
Section: Iscussion Benefitsmentioning
confidence: 97%
“…Recently much has been written on participation in asynchronous discussion (Gerbic, 2006;Thompson and Savenye, 2007) including the effects of participation levels on learning outcomes, the relationship between participation levels and student satisfaction with the online class and the factors affecting participation levels. Webb et al (2004) established a correlation between participation in asynchronous discussion forums and how well learners perform during assessments in online learning.…”
Section: IImentioning
confidence: 99%
“…Both contributing and attending to discussion messages are important activities in realizing the theoretical potential of online discussions to support knowledge construction (Wise, Speer, Marbouti, & Hsiao, 2013). However a substantial research base shows that in actual asynchronous discussions learners often pay limited attention to others' posts (Hewitt, 2003;Thomas, 2002), resulting in conversation patterns that can be characterized as incoherent rather than dialogic (Herring, 1999;Webb, Jones, Barker, & van Schaik, 2004). Early research into these problems reported disturbingly low overall statistics, suggesting that the problems were global and, to some extent, systemic products of asynchronous discussion environments (Hewitt, 2003;Kear, 2001;Swan, 2003).…”
Section: Introductionmentioning
confidence: 99%